Echoes of the Anthropocene: Reimagining Legal Consciousness in the Face of Ecological Crisis - Kapartziani, Chrysoula (European Scientific Journal, ESJ, 2024)
The concept of the “Anthropocene,” referring to the interconnection between human activity and what was once considered the natural environment, has emerged as a direct response to the radical changes in climate and ecosystems that have transformed the planet’s ecology and potentially contributed to the pandemic crisis. Human agency, long regulated through legal instruments, now takes centre stage in the management and stewardship of the planet. Law, as both a reservoir of emotionally significant social symbols and a powerful regulatory tool, plays a crucial role in this context. Therefore, understanding the evolution of environmental legal frameworks is essential. This understanding encompasses the relationship between law, society, the environment, and the role of the citizen, encapsulated in the concept of “legal consciousness”. Moreover, law operates through conceptual categories and frameworks that construct, communicate, and interpret social and cultural relationships. Given that the Anthropocene is not only an ecological condition but also a state of consciousness, environmental awareness must align with legal consciousness. This moment offers an opportunity to reshape legal culture. Several questions arise: How have legal frameworks been reflected in the words, actions, and interpretations of ordinary citizens? Is it necessary to rewrite legal terminology or redefine legal values and frameworks to depict the interconnection between nature and human activity? What role, if any, does the educational system and media play in shaping this consciousness? This paper employs a theoretical and interpretative methodology, drawing on legal theory, environmental history, and analysis of legal consciousness, to examine the role of law in shaping human responses to the environmental crises of the Anthropocene. Furthermore, what are the most effective ways to communicate contemporary legal principles, such as the rights of nature? Should these rules be developed through open and participatory processes? Finally, what lessons can be drawn from environmental history to inform future legal frameworks and values? These questions guide the exploration of how legal systems must evolve in response to the challenges of the Anthropocene.